A historical overview of the appearance and spread of Musa pests and pathogens on the African continent: highlighting the importance of clean Musa planting materials and quarantine measures - Blomme, Guy; Ploetz, R.; Jones, D.; Langhe, E. de; Price, N.; Gold, C.; Geering, A.; Viljoen, Altus; Karamura, D.; Pillay, M.; Tinzaara, William; Teycheney, P.Y.; et al. (Wiley, 2013)
The genus Musa is not native to Africa. It evolved in tropical Asia, from southwest India eastward to the island of New Guinea. There is a growing circumstantial evidence which suggests that the East African Highland banana and the tropical lowland plantain were cultivated on the African continent since before 1 AD. It is also probable that ABB cooking and AB and AAB dessert cultivars were brought to the continent from India by Arabian traders from 600 AD, and that these were disseminated throughout East Africa. During the colonial era, the main centres of distribution for banana cultivars were botanical gardens, such as Zomba in Malawi, Entebbe in Uganda and Amani in Tanzania. It appears that the very early introductions of Highland banana and plantain arrived in Africa as a relatively clean material without the conspicuous pests and diseases that affect them in Asia. In contrast, several devastating problems now impact the crop in Africa, including nematodes, the borer weevil and diseases, most notably banana bunchy top, banana streak, Sigatoka leaf spots, Xanthomonas wilt and Fusarium wilt. We (a) provide chronological overviews of the first reports/observations of different Musa pests and pathogens/diseases in Africa, (b) highlight specific examples of when a pest or pathogen/disease was introduced via planting materials and (c) give recent examples of how the pests and pathogens spread to new regions via planting materials. In total, these production constraints threaten banana and plantain production throughout the continent and impact those who can ill afford lost production, the small‐holder producer. Our intent in this review is to highlight the significance of these problems and the great importance that infested planting materials have played in their development.